2006
DOI: 10.1002/chem.200600127
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Theoretical Investigation of Gas‐Phase Reactions of Ca2+with Glycine

Abstract: The gas-phase reactions between Ca(2+) and glycine ([Ca(gly)](2+)) have been investigated through the use of mass spectrometry techniques and B3-LYP/cc-pWCVTZ density functional theory computations. The major peaks observed in the electrospray MS/MS spectrum of [Ca(gly)](2+) correspond to the formation of the [Ca,C,O(2),H](+), NH(2)CH(2) (+), CaOH(+), and NH(2)CH(2)CO(+) fragment ions, which are produced in Coulomb explosion processes. The computed potential energy surface (PES) shows that not only are these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 34 publications
9
78
0
Order By: Relevance
“…Also, in agreement with the behavior reported for serine, 25 the global minimum of the [Sec-Ca] 2+ PES is a CS structure, what is at variance with glycine, 46 where the global minimum of the PES is a SB structure. The interconversion between local minima of the [Sec-Ca] 2+ PES is reported in Figure 4.…”
Section: Conversely Complexes B(z) D(z)-f(z)supporting
confidence: 75%
“…Also, in agreement with the behavior reported for serine, 25 the global minimum of the [Sec-Ca] 2+ PES is a CS structure, what is at variance with glycine, 46 where the global minimum of the PES is a SB structure. The interconversion between local minima of the [Sec-Ca] 2+ PES is reported in Figure 4.…”
Section: Conversely Complexes B(z) D(z)-f(z)supporting
confidence: 75%
“…It is well known that the most stable gas-phase [Ca-Gly] 2+ isomer exhibits Gly in its zwitterionic state [60]; however, structural information on the remaining [Ca-AA] 2+ ion complexes is scarce. Thus, we simulated the [Ca-AA] 2+ ion complexes, in which the AAs are both in their neutral and zwitterionic state.…”
Section: (Iii) Additional Notes On Adsorption Energiesmentioning
confidence: 99%
“…Several studies report this methodology to determine the strength of binding of metal cations and ligands. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][38][39][40][41][42][43][44][45][46][47] …”
Section: Resultsmentioning
confidence: 99%
“…Yánez et al 34 extensively studied the interaction of metal cations with O-, N-and S-coordinating ligands. [31][32][33][34] Geometrical, electronic and energetic characteristics of the complexes and the isolated ligands were rationalized to explain metal-ligand affinity trends. It was found that the peripheral groups bonded to the anchoring atom that binds to the metal cation modulate the interaction strength.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation